THE EFFECT OF THE PJBL-STEM MODEL ON CREATIVE THINKING SKILL ON SCIENCE LEARNING - Rahmadani, Annisa; Muttaqiin, Arief; Evita Putri, Rahmah (ISER (Indonesian Science Education Research), 2024)
This scientific writing assignment investigates the impact of the PjBL-STEM model on students' creative thinking abilities in the context of the education system in Indonesia. This research focuses on 21st Century learning skills, namely creative, critical and process. One of the learning models recommended by the government is Project Based Learning (PjBL). In order to combine contextual with project assignments and to achieve 21st century skills, it is necessary to implement the PjBL model with a STEM (Science, Technology, Engineering and Math) approach. The methodology of this study involves a systematic literature review of 8 articles published in the last ten years. The findings of the study show that the PjBL-STEM model not only improves students' creative thinking abilities but also deepens their understanding of concepts, increases their active involvement in learning, and improves their ability to apply knowledge in various situations. The study concluded that the PjBL-STEM model is more effective than conventional teaching methods in improving students' creative thinking abilities. Keywords: PjBL-STEM, Science, Creative, Thinking, Ability